Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1097/01.hjh.0000226210.95936.bc
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in hypertension management in England: results from the Health Survey for England 2003

Abstract: Hypertension management has improved greatly since 1994, with more awareness, treatment and control. Nevertheless, in 2003 the majority of hypertensive adults in England had blood pressure levels above the currently recommended targets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
178
4
7

Year Published

2007
2007
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(208 citation statements)
references
References 12 publications
15
178
4
7
Order By: Relevance
“…17 In particular, the lack of improvement in SBP may prevent the patients to receive the benefits of otherwise improved hypertension care. Compared with the prevalences of hypertension in our study, those reported since 2000 in other studies by age and sex have been lower in most, [18][19][20][21][22][23][24][25][26][27] but not in all populations. 27,28 As in our paper, the rate of awareness of hypertension in these reports was usually more than 60%.…”
Section: Discussioncontrasting
confidence: 90%
“…17 In particular, the lack of improvement in SBP may prevent the patients to receive the benefits of otherwise improved hypertension care. Compared with the prevalences of hypertension in our study, those reported since 2000 in other studies by age and sex have been lower in most, [18][19][20][21][22][23][24][25][26][27] but not in all populations. 27,28 As in our paper, the rate of awareness of hypertension in these reports was usually more than 60%.…”
Section: Discussioncontrasting
confidence: 90%
“…In fact, the recently published report of the 2003 HSE revealed that the number of patients on X2 antihypertensive agents had increased to 56% since 1998. 39 In view of the results of the present study, future guidelines may need to focus on encouraging the initiation and continuation of antihypertensive therapy, to ensure that all hypertensive patients are adequately treated.…”
Section: Treatment Of Hypertensive Patients With X3 Additional Risk Fmentioning
confidence: 93%
“…42 Risk estimating systems such as SCORE are increasingly important considering the overall failure of medical practice to achieve substantial reductions in cardiovascular risk in Europe. 39,[44][45][46][47][48] This study demonstrates that dyslipidaemia may often go unrecognized in hypertensive individuals. Moreover, our results indicate a significant gap between treatment guidelines and actual clinical practice.…”
Section: Treatment Of Hypertensive Patients With X3 Additional Risk Fmentioning
confidence: 99%
“…Large patient studies in industrialized countries have found relatively low proportions (27-34%) of hypertensive patients with fully controlled BP, although a few surveys do show better results (48-63%). [18][19][20][21][22][23][24][25] Quantitative data on BP control among hypertensive patients treated in middle-and lowincome countries are more limited and certainly no better (19.5-44.4%). [26][27][28][29][30][31] A recent systematic review of the literature found no significant differences in mean prevalence, awareness, treatment and control of hypertension between developing and developed countries.…”
Section: Discussionmentioning
confidence: 99%